The Effect of Scramble Learning Model on Student Learning Outcomes - Yuliana, Yuyun; Nurhayati, Enung (JLER (Journal of Language Education Research), 2025)
The issue of inferior learning results resulting from the learning process's propensity to employ less creative learning models serves as the backdrop for this study. This study aims to identify the effect of the scrumble learning model on learning outcomes. This research method uses literature reviews from 3 databases, namely Google Scholar, Garuda Portal, and ERIC using the keywords "Scramble Model", "Learning Outcomes",. The inclusion criteria are articles published in 2019-2023, free full text, there is a publisher name, volume and issue and are included in the experimental design. The results of this literature review found 8 articles discussing the impact of instructional approaches on the learning outcomes of student. All articles show that the scrumble method can improve student learning outcomes as evidenced by the increase in post-test scores from pre-test scores. The study's findings suggest that using the scramble learning paradigm can encourage student collaboration and produce a positive learning environment so that teachers can apply the scramble learning model to enhance the academic performance of students